Inventory of potential spice plants as care cosmetics - Florentina Rahayu Esti Wahyuni; Yakobus Bustami; Benediktus Ege (JPBIO (Jurnal Pendidikan Biologi), 2023)
This research is motivated by the absence of previous research that examines the use of spice plants as care cosmetics by the people of Belonsat Village. This result can make vanished of knowledge about the efficacy of spice plants as care cosmetics, so it is necessary to have a instrument used to document in writing about spice plants used as care cosmetics by the people of Belonsat Village. This study aims to 1) identify the types of spice plants that are used as care cosmetics, 2) identify parts of spice plants that are used as care cosmetics, 3) identify how to use them as care cosmetics. The research uses a qualitative descriptive approach, the research method used is a survey. The source of the data from this research was obtained from the main informant who also served as a key informant. Data obtained through in-depth interviews and participatory observation. The results of an interview with a key informant as well as a key informant showed that there were 11 species of spice plants that have the potential as care cosmetics. These spice plants include: basil, cardamom, kencur, temu giring, ginger emprit (ginger rice), elephant ginger, red ginger, temulawak, lime, orange chili sauce, and garlic. There are uses that are singular, there are also those that must be combined.